USING CHORAL READING STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION ACHIEVEMENT - Mulyani, Destia Dwi; Trilestari, Kuntum; OktaBella, Delima (Universitas Muhammadiyah Palembang, 2024)
This study aimed to enhance reading comprehension achievement of seventh graders by implementing choral reading strategy. The research was conducted with seventh-grade students from SMP Setia Darma Palembang, totaling 31 participants. The study used both a pretest and a posttest as instruments. Initially, the researcher administered the pre-test, followed by a treatment using choral reading, and concluded with the post-test. To analyze the data, a One Sample T-test was employed. The results showed a mean difference of -23.03226, a standard deviation of 8.64285, and a standard error mean of 1.55230. The lower and upper differences were -26.20248 and -19.86203, respectively, with a degree of freedom (df) of 30. The two-tailed significance (Sig) value was .000, which is less than the 0.05 significance level. The t-table value was -14.837, which is much greater than the critical value of 1.697 for 31 subjects. This indicates a significant improvement in students' reading comprehension achievement after using choral reading.